TERORISME DI INDONESIA: - M Zaki Mubarok (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
This paper explores some factors that brought about the involvement of three subjects in 2009 terrorist attack, namely Afham, Sonny (both were students of UIN Syarif Hidayatullah Jakarta), and Fajar (was an alumnus of the same university). Their involvement in the act of terrorism was manifested by an attempt to protect two fugitive suicidal terrorists of JW Marriot and Ritz Carlton Hotels in 2009, namely Saifuddin Zuhri and M. Syahrir. The study employed qualitative design where the data were gained through in-depth interviews with the subjects and their parents. This study found three essential factors influencing their roles in such terrorist activities, i.e. kinship, friendship, and religious activities.